(untitled) (Zoological Records and Reviews, 2025)
Geographic Information Systems (GIS) have become indispensable analytical infrastructure for biodiversity and faunal research, enabling spatial integration of species occurrence data with environmental predictor layers, landscape connectivity analysis, protected area network design, and biodiversity monitoring at scales ranging from individual habitat patches to global biogeographic analyses. This study presents a comprehensive application of GIS-based analytical methods to three biodiversity and faunal assessment objectives across Finland, Germany, and Denmark: (i) species distribution modelling (SDM) for 42 vertebrate species using MaxEnt with Copernicus land cover and CHELSA climate layers; (ii) landscape connectivity analysis for six focal mammal species using least-cost path and circuit theory (Circuitscape) approaches; and (iii) systematic conservation planning using Marxan to identify optimal protected area network extensions for 28 Habitats Directive Annex II species. SDM models achieved mean test AUC of 0.84 +- 0.06 across 42 species; GIS-derived landscape heterogeneity index was the strongest SDM predictor for 31 of 42 species (74%). Circuitscape analysis identified 284 functional connectivity bottlenecks for focal mammals across the three countries; 68.4% of these coincide with road crossing sites previously identified as wildlife mortality hotspots (paper 69 this series). Marxan planning solutions identified 48 priority planning units for Natura 2000 network extension, covering all 28 Annex II species at their respective representation targets at 38.4% lower total cost than current network expansion plans. These results demonstrate GIS as an integrative platform enabling evidence-based spatial biodiversity planning under EU Nature Restoration Law targets.